Determinants Of Peri-Operative Blood Transfusion In A Contemporary Series Of Open Prostatectomy For Benign Prostate Hyperplasia. - Kyei, M.Y.; Klufio, G.O.; Mensah, J.E.; Gepi-Attee, S.; Ampadu, K.; Toboh, B.; Yeboah, E.D. (BMC Urology, 2016)
Background: The objective of this study was to determine the factors responsible for peri-operative blood transfusion in a contemporary series of open prostatectomy for benign prostate hyperplasia and thus offer a guide for blood product management for the procedure. Methods: This was a prospective study of 200 consecutive patients who underwent open prostatectomy for BPH from January 2010 to September 2013 at the Korle Bu Teaching Hospital, Accra. The data analyzed included the pre-operative blood haemoglobin level (Hb), presence of co-morbidities, the case type, indication for the surgery, ASA score, anaesthetic method used, systolic blood pressure, status of the operating surgeon, duration of surgery and the operative prostate weight. The transfusion of blood peri-operatively was also documented. Results: The mean age of the patients was 69.1 years. Elective cases formed 83.5 % with refractory retention of urine being the commonest indication for surgery (68.0 %). The mean pre-operative Hb was 12.1 g/dl. Consultants performed 56.0 % of the prostatectomies. Transvesical approach was used in 90.0 % of the cases. The mean operative time was 101.3mins (range 35.0–240.0) with a mean operative prostate weight of 110.8 g (range 15–550 g). Most of the patients (82.0 %) had spinal anaesthesia. The blood transfusion rate was 23.5 %. The transfusion rate was significantly higher in patients with anaemia (p = .000), emergency cases (p = .000), the use of general anaesthesia (p = .002), a resident as the operating surgeons (p = .034), prostate weight >100 g (p = .000) and duration of surgery (p = .011). In a multivariable logistic regression analysis however only the pre-operative Hb (p = .000. OR 0.95, 95 % CI [0.035–0.257]) and the duration of surgery (p = .025, OR 1.021, 95 % CI [1.003–1.039]) could predict blood transfusion in open prostatectomy for BPH in this series. Conclusions: A ‘group and save’ policy should be the preferred blood ordering procedure for patients with Hb ≥ 13.0 g/dl scheduled for an elective open prostatectomy for BPH under spinal anaesthesia. A long operative time however may increase the need for blood transfusion.
Research Article
Keywords: Blood Transfusion; Prostatectomy; Benign Prostate; Hyperplasia